LCIRAH Presentation: PoSHAN policy process. - Webb, Patrick, 1959- (Tufts University. Tisch Library., 2017)
LCIRAH conference presentation, given in June 2014.; Keywords: The presentation details the PoSHAN Policy study being conducted in Nepal by the Nutrition Innovation Lab and what it hopes to quantify.; Keywords: LCIRAH, PoSHAN, PoSHAN Policy, quanitifying government2012- NIL, 2014 Food and Nutrition Bulletin.; NIL Presentations 2013-2015.